A Field Observation on Lightning Performance Improvement of Overhead Distribution Lines - Zoro, Reynaldo; Mefiardhi, Ryan; Hidayat, Syarif; Mardiana, Redy (ITB Journal Publisher, LPPM ITB, 2009)
Two feeders of 20 kV overhead distribution lines which are located in a high lightning density area are chosen to be observed as a field study due to their good lightning performance after improvement of lightning protection system. These two feeders used the new overhead ground wire and new line arrester equipped with lightning counter on the main lines. The significant reduced of lines outages are reported. Study was carried out to observe these improvements by comparing to the other two feeders line which are not improved and not equipped yet with the ground wire and line arrester. These two feeders located in the nearby area. Two cameras were installed to record the trajectory of the lightning strikes on the improved lines. Lightning peak currents are measured using magnetic tape measurement system installed on the grounding lead of lightning arrester. Lightning overvoltage calculations are carried out by using several scenarios based on observation results and historical lightning data derived from lightning detection network. Lightning overvoltages caused by indirect or direct strikes are analyzed to get the lightning performance of the lines. The best scenario was chosen and performance of the lines were improved significantly by installing overhead ground wire and improvement of lightning arrester installation.